Homocysteine-induced enhancement of spontaneous contractions of myometrium isolated from pregnant women - Ayar, A; Celik, H; Ozcelik, O; Kelestimur, H (Blackwell Munksgaard, 2003)
Background. Although many associations have been demonstrated between hyperhomocysteinemia and pregnancy complications, such as spontaneous abortion, preterm labor, preeclampsia and low birthweight, it is still not clear whether hyperhomocysteinemia is the cause or the consequence of these pregnancy complications. The aim of this study was to investigate the effects of homocysteine on the spontaneous contractility of isolated pregnant human myometrium. Methods. Myometrium samples obtained from women undergoing elective caesarean section were suspended in a jacketed organ bath containing Krebs' solution at 37degreesC (pH 7.4), continuously gassed with 95% O-2 and 5% CO2 . After manifestation of spontaneous contractions under 2 g of resting tension, homocysteine was applied to the organ bath, and amplitude and frequency of contractions were evaluated at 20-min intervals. Statistical analysis of amplitude and frequency of the contractions was performed using the Kruskal-Wallis analysis of variance test. Results. Application of 0.1 mm homocysteine had no significant effect on either frequency (4.63 +/- 0.42 vs. 4.01 +/- 0.53 for the control period; p > 0.05) or amplitude (3.20 +/- 0.07 g vs. 3.15 +/- 0.07 g; p > 0.05) of spontaneous contractions, while 1 and 2 mm homocysteine significantly increased the frequency (8.54 +/- 0.62 vs. 3.9 +/- 0.44, p < 0.02, and 12.32 +/- 0.72 vs. 3.96 +/- 0.51, p < 0.001, respectively) of spontaneous contractions but caused only a modest change in amplitude (2.92 +/- 0.04 g vs. 2.87 +/- 0.05 g, p > 0.05, and 3.02 +/- 0.06 g vs. 2.93 +/- 0.05 g, p > 0.05, respectively). Conclusion. Results from this study indicate for the first time that homocysteine causes enhancement of spontaneous contractions of myometrium derived from pregnant women.
Keywords: homocysteine; myometrium; preterm delivery; human